Acceleration of Circular Economy Based on Waste-to-Wealth Toward Environmental Sustainability - Septa Rahmadi, Didin septa; Jannah, Wardatul; Purwati, Duwi; Suanda, I Wayan; Sukendra, I Komang (Abdi Masyarakat, 2025)
The transition toward a circular economy has become essential in addressing environmental challenges and economic limitations in resource-based rural communities. Bentek Village, North Lombok Regency, faces persistent problems related to unmanaged bamboo waste generated from satay stick industries, which poses environmental risks and lacks economic value. This community service program aimed to accelerate the implementation of a waste-to-wealth–based circular economy by enhancing technical capacity, social entrepreneurship, and digital marketing skills. The target partners were the Kelompok Tani Hutan (KTH) “Lengkah Pangkok” and the youth organization Karang Taruna “Bareng-Bareng,” involving 40 participants. The program employed a participatory action research approach through stages of socialization, focus group discussions, training on bamboo waste processing into organic fertilizer and bio-briquettes, social entrepreneurship strengthening, infrastructure development, and continuous mentoring and evaluation. The results indicate an average competency improvement of 40.3% based on pre-test and post-test analyses, covering technical knowledge, social entrepreneurship, and digital marketing competencies. Qualitatively, the program enhanced environmental awareness, community participation, the establishment of two new waste-based business units, and reduced bamboo waste by approximately 60%. These findings demonstrate that a community-based circular economy approach is effective in promoting social empowerment, economic resilience, and environmental sustainability at the village level.